The Usage of Finite Element Method (FEM) of Pore Water Pressure Simulation for Earth Fill Dam from Field Investigation - SITTHIVONG, Phouthamala; TANCHAISAWAT, Tawatchai; LAOSUWAN, Sirikanya; LORSAVANH, Souksavath; SIMMAVONG , Khongseng; CHANSAVANG , Bounsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research paper investigated the analysisthe pore water pressure model at Mae Ngat Somboon Chon Dam. Data were collected from field instrumentation and finite element method analysis of 2D plane strain non-linear by considering the parameters of the soil properties at the dam’s construction. The Incremental Model was applied to analyze both the static analysis under hydrostatic pressure and the self – weight analysis. In order to simulate the behavior of water pressure that occurs within the dam, field instrumentation of electric piezometer , which the study adopted plane strain non-linear finite element analysis. The Elasto-Plastic with Mohr Coulomb failure criteria was used in soil properties of modelling in 2D plain strain mode, sensitivity analysis of soil properties at random zone were performed by mean of back calculation in hydrostatic condition and under hydrostatic pressure. From the analysis of the Incremental Model under the static pressure compared to the actual dam and estimated pore water pressure from a 2D simulation with Finite Element Method. In the area of embankment dam to find the nearest field instrumentation of electric piezometer pore water pressure. It can be concluded that the appropriate soil parameters used in finite element analysis can be predicted well compared to field instrumentation. Furthermore, the value permeability has effected pores water pressure by finite element analysis. The comparison result of the pore water pressure that is installed by the detector Electric Piezometer at any locations and the pore water pressure that analyze by finite element shows that the water is able to flow into the soil in the Random Zone and Core Zone of the dam, which is adjacent to the Foundation of dam, where the water has passed through the static. This causes the water pressure increased as point where the water passes through the constant.